Unlocking the Power of Financial Experience: How Risk Perception Shapes Investment Decisions - Redawati, Redawati; Hayat, Atma (Accounting and Finance Studies, 2024)
Research Aims: This study aims to investigate the influence of financial experience on investment decisions, with risk perception acting as an intervening variable among stock investors in Banjarmasin. Design/methodology/approach: The research employs a Partial Least Squares Structural Equation Modeling (PLS-SEM) approach to analyze the data collected through a survey questionnaire distributed to 122 stock investors in Banjarmasin. This methodology allows for simultaneous analysis of direct and indirect relationships between variables, providing a comprehensive understanding of the dynamics influencing investment decisions. Research Findings: The findings indicate that financial experience significantly and positively affects investment decisions, suggesting that investors with more extensive financial experience are likely to make more informed and strategic choices. Furthermore, financial experience significantly impacts risk perception, which in turn influences investment decisions, underscoring the crucial role of risk perception as a mediator in this relationship. Theoretical Contribution/Originality: This study contributes to the behavioral finance literature by elucidating the relationship between financial experience, risk perception, and investment decisions. It highlights the importance of financial literacy and education in enhancing investment decision-making processes, thereby promoting more rational and independent investment choices. Keywords: Financial experience, investment decisions, risk perception, behavioral finance, PLS-SEM